The origin of the Lithuanian illative - Hill, Eugen (Baltistica, 2020)
The paper deals with the origin of the Lithuanian illative case. The illative, found in Lithuanian since the very begin of its text records in the early 16th c., is a recent formation which, in the given form, may have emerged as late as after the disintegration of Proto-East-Baltic. In both numbers the illative case-forms of Lithuanian nouns emerged out of directional adverbs, which were in turn based on adverbially used case-forms of nouns. The marker of the Lithuanian illative is an inherited suffix of directional adverbs which is also attested in Germanic, Italic and probably also Tocharian. The situation in Tocharian makes it probable that the marker of Lithuanian illative was originally used for deriving adverbs not with primarily directional but rather with perlatival semantics.